Executive Compensation, Executive Character, Audit Committee, and Audit Quality on Tax Avoidance - Kenny Ardillah; Agus Prasetyo C (Department of Accounting-Faculty of Economic and Business (FEB), 2021)
Tax avoidance turns into become most part satisfactory tax assessment practice, despite the fact that the practice isn’t in opposition to the law that can’t be acknowledged , should be forestalled, and gone against. This study expect to inform the impact of executive compensation, executive character, audit committee and audit quality on tax avoidance of mining companies listed on the Indonesia Stock Exchange. The sample selection method in this study uses purposive sampling. The sample of this study is mining companies listed on the Indonesia Stock Exchange. The data analysis technique used in this study is multiple linear regression. The results of this study proved that executive character has positive effect on tax avoidance and executive compensation, audit committee, and audit quality have no effect on tax avoidance. This research is required to be the reason for decision making by the management to not to rehearse tax avoidance and make thought for investor to not settle on speculation choices dependently on the evaluation of corporate governance perspectives that don’t influence the organization in carrying out tax avoidance practice.How to Cite:Ardillah, K., & Prasetyo C, A. (2021). Executive Compensation, Executive Character, Audit Committee, and Audit Quality on Tax Avoidance. Akuntabilitas: Jurnal Ilmu Akuntansi, 14(2), 169-186.